A note on the variance of generalized first order autoregressive processes with moving average errors - Shitan, Mahendran (InterStat, 2008)
A new class of time series models known as Generalised Autore-gressive of order one with flrst order moving average errors has been introduced in order to reveal some hidden features of certain time se- ries data. A closed form of the variance of the process is derived. It is shown that in special cases this new result reduces to the standard ARMA results.